Prevalence of Thinness Among Rural Pre-school Children of East Midnapur, West Bengal, India. - Mandal, Gopal Chandra; Acharya, Atanu; Bose, Kaushik (Asian Journal of Biological and Life Sciences, 2012)
Nutrition during the first five years has not only an impact on growth and morbidity during childhood, but also acts as a determinant of nutritional status in adolescent and adult life. India has the highest occurrence of childhood malnutrition in the world. Body mass index (BMI) has been used for assessing thinness more recently in children aged 0-5 years.The aim of the present study was to evaluate the different grades of thinness among the Bengalee preschool Integrated Child Development Services Scheme (ICDS) children. This cross sectional study was conducted in nine villages of Argoal Gram Panchayat at 10 (ten) ICDS centers of Purba Medinipore, West Bengal. The total sample was 225 between the age group 3 and 6 years. Thinness was evaluated by using age and sex specific internationally accepted cut off points. The overall prevalence of thinness was 59.1%. The boys were comparatively (61.8%) more malnourished than girls (56.8%). This difference was statistically significant (χ 2 = 7.18, d.f. 1; p < 0.025).From the present study it can be concluded that, the rural preschool children were found to be highly malnourished, but this situation was comparatively better than the rural children from the ICDS centers of Hooghly and Purulia Districts. These results indicate that the present food supplementation programme of the ICDS centers is inadequate.